Application of Animation Media in Improving the Language of Children Age 5 - 6 Years Elim Sawinggrai Kindergarten, Raja Ampat District - Roike Mambrasar; Ismail Marzuki; Yolan Marjuk; Neng Sih Sri Wahyuni (MultiTech Publisher, 2023)
The Bela Bangsa Mandiri Kindergarten is focusing on language development for children aged 5-6 years. Animated learning media is used to convey information effectively, improving language skills. However, the school's implementation has not been optimal due to inadequate facilities and infrastructure. This research aims to determine the application of animation media in improving language skills in children aged 5-6 years. The study involved a teacher and 20 students, with data collected through observation, interviews, and documentation. The results showed that the application of animation media involves choosing a theme, preparing the media, focusing attention, providing material based on psychological principles, stimulating abilities, and providing evaluation. The study found that 20% of the students were not yet developing.